EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STRUCTURED NUMBERED HEADS (SNH) DAN PROBLEM BASED LEARNING (PBL) DENGAN PENDEKATAN SAINTIFIK PADA MATERI POKOK BILANGAN DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS VII SMPN DI KABUPATEN KEBUMEN - Muslikhah Muslikhah; Mardiyana Mardiyana; Dewi Retno Sari Saputro (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from students self regulated learning (SRL). The learning model compared were SNH with scientific approach, PBL with scientific approach and classical with scientific approach. This research used quasi-experimental research  with 3x3 factorial design. The population were all seventh grade students of SMPN  in Kebumen on academic year 2014/2015. This research used stratified cluster random sampling technique and sample consisted of students of SMPN 3 Kebumen, SMPN 7 Kebumen, SMPN 1 Sruweng. The instruments used were documentation, questionnaire, and test. The data analysis technique was used unbalanced two ways anova at the significance level of 0.05. Based on the data analysis, it can be concluded as follows. (1) SNH with scientific approach gives better achievement than PBL and classical with scientific approach, and PBL with scientific approach gives better achievement than classical with scientific approach. (2) Students who have high SRL have better achievement than students who have medium and low SRL,  students who have medium SRL have better achievement than students who have low SRL. (3) For SNH with scientific approach, students who have high and medium SRL have the same achievement, students who have high SRL have better achievement than students who have low SRL, students who have  medium and low SRL have the same achievement. For PBL and classical with scientific approach students who have high SRL have the same achievement with students who have medium and low SRL, students who have medium and low SRL have the same achievement. (4) For high SRL of the students, SNH and PBL with scientific approach gives the same achievement, SNH with scientific approach gives better achievement than classical with scientific approach, PBL and classical with scientific approach gives the same achievement. For medium and low SRL of the students, SNH with scientific approach gives the same achievement with PBL and classical with scientific approach, PBL and classical with scientific approach gives the same achievement.Keywords: SNH, PBL, Scientific Approach, Self Regulated Learning (SRL)